Visible Light Photocatalytic Properties of Ta and N Codoped SrTiO3 Nanoparticles - Uyi Sulaeman; Shu Yin; Tsugio Sato (International Journal of Optics)
Ta and N co-doped SrTiO3 was synthesized by microwave-assisted solvothermal reaction using SrCl2⋅6H2O, Ti(OC3H7)4, TaCl5, and HMT (hexamethylenetetramine) in KOH and oleic acid mixed solutions. The products were characterized by XRD, TG-DTA, BET surface area measurement, TEM, EDX, DRS, PL-Spectra, and XPS. The nanoparticles of perovskite-type SrTi1-xTaxO3-yNy (x=0−0.1) were successfully synthesized. The photocatalytic activity of SrTiO3 for DeNOxability in the visible light region could be improved by the codoping of Ta5+ and N3-. The excellent visible light photocatalytic activity of this substance may be due to the generation of a new band gap by doping nitrogen that enables the absorption of visible light as well as a decrease in the incidence of the lattice defects, which acts as a recombination center of photo-induced electrons and holes by codoping with Ta5+.